Examining the Determinants of Residential Real Estate Prices. Evidence from Poland - Ruszuk, Michał; Spirzewski, Krzysztof (Badanie determinant cen nieruchomości mieszkaniowych. Przykład Polski, 2024)
Aim: The aim of the research is to provide a comprehensive account of the determinants of residential property prices in particular the financial ones. This is an important issue for the Central Bank as well as for commercial banks, as the financing of the housing market is an important factor for conducting monetary policy as well as for assessing the level of credit risk. Methodology: An empirical survey method based on the pooled least squares (OLS) estimation model was used. Data published by the Central Statistical Office and the AMRON-SARFiN Centre were used. They were aggregated for voivodeships and quarters for the period 2010-2019. Findings: The result of the analysis allows researchers of this topic as well as practitioners to identify the priority determinants of residential property prices in Poland, which turned out to be the financial factor, i.e. income (average monthly earnings) and demographic factor (new marriages). Originality/Value: The main research’s value is the identification of the other analysed determinants, such as the cost of construction, interest rates and the supply of houses, as insignificant determinants of prices in the Polish real estate market in the periods under study.
Financial Sciences. Nauki o Finansach, 2024, vol. 29, no. 1, s. 37-64
Keywords: financing residential real estate; price determinants; bank; finansowanie nieruchomości mieszkaniowych; determinanty cenowe